Insights into the biodegradation of polycaprolactone through genomic analysis of two plastic-degrading Rhodococcus bacteria - Zampolli, Jessica; Vezzini, Daniele; Brocca, Stefania; Di Gennaro, Patrizia (Frontiers in Microbiology, 2024)
Polycaprolactone (PCL) is an aliphatic polyester often utilized as a model to investigate the biodegradation potential of bacteria and the involved catabolic enzymes. This work aims to characterize PCL biodegradative metabolic potential and correlate it to genomic traits of two plastic-degrading bacteria: Rhodococcus erythropolis D4 strain, a new isolate from plastic-rich organic waste treatment plant, and Rhodococcus opacus R7, known for its relevant biodegradative potential on polyethylene and similar compounds.After preliminary screening for bacteria capable of hydrolyzing tributyrin and PCL, the biodegradation of PCL was evaluated in R. erythropolis D4, and R. opacus R7 by measuring their growth and the release of PCL catabolism products up to 42 days. After 7 days, an increase of at least one order of magnitude of cell number was observed. GC-MS analyses of 28-day culture supernatants showed an increase in carboxylic acids in both Rhodococcus cultures. Furthermore, hydrolytic activity ( 5 U mg -1 ) on short/medium-chain pnitrophenyl esters was detected in their supernatant.Finally, genome comparative analysis has been performed between two Rhodococcus strains and comparison with genes annotated in reference strains revealed hundreds of gene products putatively related to polyester biodegradation. Based on additional predictive analysis of gene products, gene expression was performed on a smaller group of genes, revealing that exposure to PCL elicits the greatest increase in transcription for a single gene in strain R7, and two genes, including that encoding a putative lipase, in strain D4.This work exhibits a multifaceted experimental approach to exploit the broad potential of Rhodococcus strains in the field of plastic biodegradation.